HUBUNGAN FAKTOR SOSIAL DAN LINGKUNGAN BELAJAR TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS X BUSANA SMK N 1 MERANGIN - Tukini Rahmawati Rahmawati; Awatif; Hasmawati (Hiradika | Hira Institute, 2025)
The problem in this study is the low level of social factors and learning environment on student’s understanding of mathematical concepts. The purpose of this study is to describe the significant relationship between social factors and learning environment on student’s understanding of mathematical concepts. This study used a quantitative approach with a correlationa method. The sampling technique used is total sampling technique where all members of the population are sampled, so the sample is 60 students. The research instrument is a questionaire with 42 statement and 2 test item. Based on the analysis, the data is not normally distributed and has a linear pattern. The data analysis technique used to test the hypothesis is the Spearman Rank correlation, for the significance test using the F test, followed by the coeffisient of determination formula. Data analysis shows that or 122.72 > 3.172 then is rejected and is accepted. So it can concluded that there is a significant relationship between social factors and learning environment on students understanding of mathematical concepts of class X Clothing SMK N 1 Merangin.